HANK faces unemployment - Agostino Consolo; Matthias Hänsel (European Central Bank (ECB), 2024)
Since the advent of Heterogeneous Agent New Keynesian (HANK) models, countercyclical unemployment risk has been deemed an important amplification mechanism for business cycles shocks. Yet, the aggregate effects of such "unemployment fears" are hard to pin down. We thus revisit this issue in the context of a rich two-asset HANK model, proposing new ways to isolate their general equilibrium effects and tackle the long-standing challenge of modelling wage bargaining in this class of model. While unemployment fears can exert noticeable aggregate effects, we find their magnitude to depend importantly on the distribution of firm profits. Households' ability to borrow stabilizes the economy. Our framework has also implications for policy: in the aftermath of an adverse energy price shock, fiscal policy can help reducing the hysteresis effects on unemployment and most households gain if the central bank accommodates an employment recovery at the cost of higher inflation.
Keywords: D52; E24; E52; J64; 330; Heterogeneous models; search and matching models; alternating offer bargaining; monetary and fiscal policy